Biocontrol Ability of Puccinia abrupta var. partheniicola on Different Growth Stages of Parthenium Weed (Parthenium hysterophorus L.) - MOHAMAD TAUFIK FAUZI (Bogor Agricultural University, Indonesia, 2009)
A research was conducted to investigate the biological control ability of Puccinia abrupta var. partheniicola infected to parthenium weed (Parthenium hysterophorus L.) at different stages of growth in a glasshouse. The study also investigated the combined effect of the infection and the competitor plant, i.e. buffel grass (Cenchrus ciliaris L.), a pasture species usually found in the weed habitat in Central Queensland. The 2 x 3 factorial experiment was arranged in a completely randomized design with six replicates in each treatment. The parthenium weeds were planted with or without buffel grass. The plants were inoculated with P. abrupta var. partheniicola urediniospores either at the rosette, flowering or mature growth stage of development. As controls, an additional six non inoculated plants with and without buffel grass were planted. The results showed that P. abrupta var. partheniicola affected more on the younger plants than on the older ones. Its infection decreased the plant height. A higher reduction in plant above ground biomass was recorded because of the rust when the plants were inoculated at the rosette growth stage of development in the presence of competition. The impact of the rust was greatest on the ability of parthenium to produce seeds. Key words: Puccinia abrupta var. partheniicola, biological control, parthenium weed